Daylight Autonomy as a Driver for Office Building Retrofitting. (September 2016) - Raimondi, Alberto; Santucci, Daniele; Bevilacqua, Simone; Corso, Alessandro
Abstract: Daylight has always had a relevant part in design for architects and engineers since really ancient times. Even if light had such an important role in the design process, new methods for quantifying more precisely lighting levels have been discovered just in the last decade. In this research, issues related to daylight in office buildings - due to volume, structure, and orientation - have a key role. Lighting levels in workspaces are fundamental in order to estimate and optimize dimensions for an office building; the depth of the building in relation to the facade is one of the most common problems that always represent a struggle for designers that have to find a meeting point between intentions and performance. The research is particularly focused on the optimization of existing building shapes that, in accordance with new facades, optimize natural lighting levels in office spaces. The improvement of indoor comfort regarding natural lighting levels is nowadays one of the main topics in retrofitting interventions, especially in the case of office buildings environments where orientation, context and functions significantly change in relation to the orientation. The reduction of the thermal energy demand has been deeply investigated and the challenge to have nZEB retrofitting involves the reduction of energy for artificial light. Could the building depth change accordingly to a specific luminance level? How does the spatial quality of working spaces increase, if the building shape changes to get as much daylight as possible? Today, simulation software gives us the possibility to obtain precise information relatively to each environment on every single floor at any time of the year; the precision of the analysis results mostly depend on how accurate the study model is, and on how the settings have been given. Through the use of parametric software such as Grasshopper, together with potentialities offered by Ladybug and Honeybee, it is possible to obtain detailed natural lighting parameters and to explore the field of environmental analysis. In particular, starting from daylight autonomy simulations, an expansion based on daylight autonomy values has been made: the higher the percentage, the more the building extends its area. The idea is to get an extension of useful working space just in those areas in which luminance levels are acceptable for a longer time while, at the same time, buildings get slimmer where natural light conditions are worse. The concept has been tested on a study case in Rome, more specifically to the Ligini's Towers in the rationalist neighborhood of EUR.